“Incidencia de agenesia en pacientes entre 15 a 18 años en el Hospital general provincial docente Riobamba” - Martínez Once, María Belén (2017)
The following research was conducted in the service of Dentistry Provincial General Hospital of Riobamba, the universe was 137 patients in the age range of 15 to 18 who visited the service Dentistry hospital, non-probability sampling was used aspirational, being conformed the sample of 80 patients, the study variables were age, sex, education level, family history of dental agenesis, socioeconomic status and agenesis. All information obtained in the investigation was based on models of data collection in Microsoft Excel in order to obtain numbers and percentages, the results analyzed and discussed, settled in tables and graphs according to research standards, were respected all the ethical standards established in the field of scientific research established in the country, concluding that there is a higher incidence of agenesis of third molar in the population 15-18 years in study patients, females predominated, inheritance determines the presence of third molar agenesis and prevailed agenesis coincidence of temporary and permanent dentition.